Corneal curvature radius and associated factors in Chinese children: the Shandong Children Eye Study - Zhang, Yue Ying; Jonas, Jost B. (PLOS ONE, 2015)
Purpose: To investigate the distribution of the (CCR) and its associated factors in children. Methods: Using a random cluster sampling method, the school-based, cross-sectional Shandong Children Eye Study included children aged 4 to 18 years from the rural county of Guanxian and the city of Weihai in the province of Shandong in East China. CCR was measured by ocular biometry. Results: CCR measurements were available for 5913 (92.9%) out of 6364 eligible children. Mean age was 10.0±3.3 years, and mean CCR was 7.84±0.27 mm (range: 6.98 to 9.35 mm). In multivariate linear regression analysis, longer CCR (i.e. flatter cornea) was significantly associated with the systemic parameters of male sex (P<0001;standardized regression coefficient beta: -0.08;regression coefficient B:-0.04; 95% Confidence Interval (CI):-0.05,-0.03), younger age (P<0.001;beta:-0.37;B:-0.03;95%CI:-0.04,-0.03), taller body height (P = 0.002;beta:0.06;B:0.001;95%CI:0.000,0.001), lower level of education of the father (P = 0.001;beta:-0.04;B:-0.01;95%CI:-0.02,-0.01) and maternal myopia (P<0.001;beta:-0.07;B:-0.04;95%CI:-0.06,-0.03), and with the ocular parameters of longer ocular axial length (P<0.001;beta:0.59;B:0.13;95%CI:0.12,0.14), larger horizontal corneal diameter (P<0.001;beta:0.19;B:0.13;95%CI:0.11,0.14), and smaller amount of cylindrical refractive error (P = 0.001;beta:-0.09;B:-0.05;95%CI:-0.06,-0.04). Conclusions: Longer CCR (i.e., flatter corneas) (mean:7.84±0.27mm) was correlated with male sex, younger age, taller body height, lower paternal educational level, maternal myopia, longer axial length, larger corneas (i.e., longer horizontal corneal diameter), and smaller amount of cylindrical refractive error. These findings may be of interest for elucidation of the process of emmetropization and myopization and for corneal refractive surgery.
Gesehen am 04.09.2017